(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the linguistic category of neutrality in the English language, analyzing its manifestation in lexicon, grammar, and discourse. Neutrality in language is crucial for objective communication in various fields, including academic writing, journalism, and legal discourse. By examining neutrality through lexical choices, syntactic structures, and pragmatic implications, this study provides a comprehensive linguistic framework for understanding how neutrality is encoded and interpreted. The findings reveal that neutrality is often achieved through lexical ambiguity, impersonal constructions, and pragmatic strategies that minimize subjective bias. Furthermore, the study discusses the implications of neutrality for discourse analysis and sociolinguistic interactions, providing an in-depth exploration of its role in linguistic theory.